Comparison of the efficacy of diclofenac and betamethasone following strabismus surgery. Issue 4 (1st April 1997) - Wright, Mark; Butt, Zahida; McIlwaine, Gawn; Fleck, Brian
Abstract : AIMS: To compare the relative anti-inflammatory potency and safety of topical diclofenac–gentamicin with beta methasone–neomycin following strabismus surgery. METHODS: A single centre, single observer, prospective, randomised, and double masked clinical trial of 25 children undergoing bilateral symmetrical horizontal strabismus surgery was carried out. One eye received diclofenac–gentamicin and the contralateral eye received betamethasone–neomycin; both treatments were instilled four times a day for 4 weeks postoperatively. Ocular inflammation was assessed at 1 and 4 weeks postoperatively, objectively by comparison with a photographic chart and subjectively by questionnaire. RESULTS: There was no statistically significant difference in the rate of resolution of the inflammatory response between each group at both visits. CONCLUSION: Diclofenac appears to be as effective as betamethasone in controlling postoperative inflammation following strabismus surgery and may offer a safer alternative to the use of topical steroids.